Water-Protein Interactions of an Arginine-Rich Membrane Peptide in Lipid Bilayers Investigated by Solid-State NMR Spectroscopy - Li, Shenhui (2010)
The interaction of an arginine (Arg) residue with water in a transmembrane antimicrobial peptide, PG-1, is investigated by two-dimensional heteronuclear correlation (HETCOR) solid-state NMR spectroscopy. Using (13)C and (15)N dipolar-edited (1)H-(15)N HETCOR experiments, we unambiguously assigned a water-guanidinium cross peak that is distinct from intramolecular protein-protein cross peaks. This water-Arg cross peak was detected within a short (1)H spin diffusion mixing time of 1 ms, indicating that water is in close contact with the membrane-inserted guanidinium. Together with previously observed short guanidinium-phosphate distances, these solid-state NMR data suggest that the Arg sidechains of PG-1 are stabilized by both hydration water and neutralizing lipid headgroups. The membrane deformation that occurs when water and lipid headgroups are pulled into the hydrophobic region of the bilayer is symptomatic of the membrane-disruptive function of this antimicrobial peptide. The water-Arg interactions observed here provide direct experimental evidence for molecular dynamics simulations of the solvation of Arg sidechains of membrane proteins by deeply embedded water in lipid bilayers.